Chest pain–indigestion or impending heart attack?. Issue 703 (May 1984) - Simpson, F. G.; Kay, J.; Aber, C. P.
Abstract : A high proportion (40%) of patients with definite myocardial ischaemia who were questioned on admission to a Cardiac Monitoring Unit had experienced preceding chest pain which had been misinterpreted by both the patients themselves and doctors as 'indigestion' and which had often been inappropriately treated. 'Indigestion' in the chest in previously non-dyspeptic subjects over 40 years of age should be regarded as myocardial ischaemia until proved otherwise.